Pengaruh Tingkat Inflasi dan Tingkat Suku Bunga Terhadap Pertumbuhan Ekonomi di Provinsi Kalimantan Timur 2015-2023 - Siti Nurhayati (Prodi Pendidikan Ekonomi Universitas Mulawarman, 2025)
Economic growth reflects an increase in a region's production capacity, characterized by the growth of potential Gross National Product (GNP), higher output per capita, and improved living standards. Inflation and interest rates are among the key macroeconomic factors affecting economic growth. In East Kalimantan Province, the inflation rate reached its highest level of 5.35% in 2022 before declining to 3.46% in 2023. Changes in the inflation rate were accompanied by changes in interest rates, which potentially influenced economic activity and regional economic growth. This study aims to analyze the effect of inflation and interest rates on economic growth in East Kalimantan Province. The study employed a quantitative approach with an associative research design, using secondary time series data obtained from the Central Bureau of Statistics (BPS). The data were analyzed using multiple linear regression with the assistance of EViews 12 software. The results indicate that inflation has a negative and significant effect on economic growth, with a regression coefficient of −0.020, while interest rates also have a negative effect on economic growth, with a regression coefficient of −0.019. These findings suggest that increases in inflation and interest rates tend to reduce the rate of economic growth in East Kalimantan Province. Therefore, policies aimed at maintaining stable inflation and interest rates are essential to support sustainable economic growth.